2021
DOI: 10.1186/s13018-021-02248-1
|View full text |Cite
|
Sign up to set email alerts
|

Mesenchymal stem cell-originated exosomal lncRNA HAND2-AS1 impairs rheumatoid arthritis fibroblast-like synoviocyte activation through miR-143-3p/TNFAIP3/NF-κB pathway

Abstract: Background Long non-coding RNA heart and neural crest derivatives expressed 2-antisense RNA 1 (HAND2-AS1) was found to be elevated in rheumatoid arthritis (RA) fibroblast-like synoviocytes (RA-FLSs). However, whether HAND2-AS1 functions as an exosomal lncRNA related to mesenchymal stem cells (MSCs) in RA progression is unknown. Methods The expression of HAND2-AS1, microRNA (miR)-143-3p, and tumor necrosis factor alpha-inducible protein 3 (TNFAIP3) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
31
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 43 publications
(31 citation statements)
references
References 39 publications
0
31
0
Order By: Relevance
“…Moreover, the expression rates of the TNFAIP3 gene have a negative association with the RA score, anti‑cyclic citrullinated peptide (CCP) antibody, and also CRP levels [ 127 ]. Correspondingly, a study showed that long non-coding RNA heart and neural crest derivatives expressed 2-antisense RNA 1 (HAND2-AS1)-abundant MSCs- exosomes inhibited the proliferation, migration, and inflammation and also exerted the apoptosis in RA-FLS cells by the suppression of the NF-κB pathway [ 128 ]. The central role of TNFAIP3 in the regulation of the NF-κB axis was elucidated when Lee et al supposed that TNFAIP3 − / − mice quickly expired because of the systemic inflammation elicited by spontaneously activated NF-κB [ 129 ].…”
Section: Mscs-exo Applications In Regenerative Medicinementioning
confidence: 99%
“…Moreover, the expression rates of the TNFAIP3 gene have a negative association with the RA score, anti‑cyclic citrullinated peptide (CCP) antibody, and also CRP levels [ 127 ]. Correspondingly, a study showed that long non-coding RNA heart and neural crest derivatives expressed 2-antisense RNA 1 (HAND2-AS1)-abundant MSCs- exosomes inhibited the proliferation, migration, and inflammation and also exerted the apoptosis in RA-FLS cells by the suppression of the NF-κB pathway [ 128 ]. The central role of TNFAIP3 in the regulation of the NF-κB axis was elucidated when Lee et al supposed that TNFAIP3 − / − mice quickly expired because of the systemic inflammation elicited by spontaneously activated NF-κB [ 129 ].…”
Section: Mscs-exo Applications In Regenerative Medicinementioning
confidence: 99%
“…miR-222-3p/Sirt1 axis is also found to be critical for the function of lncRNA GAS5 in mitigating the proliferation, inflammation, and apoptosis of RA FLS (289). In particular, lncRNA NEAT1 and lncRNA HAND2-AS1 are found in PBMC and mesenchymal stem cells (MSC), respectively, and are involved in the regulation of RA (241,255).…”
Section: Epigenetic Targets For Treatment Of Rheumatoid Arthritismentioning
confidence: 99%
“… 60 In RA, MSC-derived exosomes are found to inhibit the activation of FLS, cells that exert a key role on the progression of RA, through miR-143-3p/TNFAIP3/NF-κB pathway, emphasizing the vital role of TNFAIP3. 61 Moreover, hypoxia-inducible factor 1α (HIF1α) is a metabolic regulator required for MSC. Silencing of HIF1α in MSC is found to increase the ratio of Th17/Tregs, associated with the metabolic alteration and reduced immunosuppressive mediators like ICAM, IL-6, and nitric oxide (NO).…”
Section: Msc Transplantationmentioning
confidence: 99%